Antibiotics for the empirical treatment of acute infectious diarrhea in children - Diniz-Santos,Daniel R. (2006)
While the routine use of antibiotics for infectious diarrhea in children must be avoided, because it brings little benefit in most cases and is associated with the risk of increasing antimicrobial resistance, selected cases may require antimicrobial therapy, and the choice of the antimicrobial agent often has to be made empirically. Physicians prescribing antimicrobials in such a setting have not only to be aware of the most likely pathogens, but also of their characteristic antimicrobial susceptibility pattern and the safety profile of the various drugs. We reviewed the literature on the use of ampicillin, beta-lactamase inhibitors, trimethoprim-sulfamethoxazole, chloramphenicol, tetracyclines, nalidixic acid, fluoroquinolones, third-generation cephalosporins, macrolides, metronidazole and malabsorbed agents in the setting of acute infectious diarrhea, and we evaluated the available information, seeking to apply it to empirical use, highlighting clinically-useful pharmacological information and patients' and pathogens' characteristics that must be taken into account for decisions about antimicrobial therapy.